2011
DOI: 10.1063/1.3610561
|View full text |Cite
|
Sign up to set email alerts
|

Surface-related two-photon absorption and refraction of CdSe quantum dots

Abstract: Colloidal CdSe quantum dots (QDs), whose surface traps are controlled with the purification process, are measured with a Z-scan technique using an 80 femtosecond pulse duration laser source. Their two-photon absorption coefficient and refractive index are decreased more than one order of magnitude with the increase of the density of surface traps, indicating that the surface states are involved in the two-photon process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…8 Several authors have already reported femtosecond measurements on colloidal CdSe QDs but the data were mostly limited to a few wavelengths. [9][10][11] Up to date, in the literature, there is only one detailed report concerning frequency degenerate and nondegenerate two-photon absorption of CdTe and CdSe QDs at wavelengths ranging from 600 to 1000 nm, 12 providing results different in magnitudes from those of Ref. 10.…”
mentioning
confidence: 90%
“…8 Several authors have already reported femtosecond measurements on colloidal CdSe QDs but the data were mostly limited to a few wavelengths. [9][10][11] Up to date, in the literature, there is only one detailed report concerning frequency degenerate and nondegenerate two-photon absorption of CdTe and CdSe QDs at wavelengths ranging from 600 to 1000 nm, 12 providing results different in magnitudes from those of Ref. 10.…”
mentioning
confidence: 90%
“…However, to date, the TPA cross-section of InP QDs has never been reported yet, which may be due to the low TPA and broad size distribution of InP QDs with poor quality. 8 Here, the TPA cross-section and two-photon excited PL properties of InP/ZnS QDs at 800 nm, a widely used wavelength in two-photon excited bio-imaging, 1 are reported. Figure 3(a) presents the two-photon excited PL spectra of QD548 and QD606 excited at 800 nm, which are almost the same as the one-photon excited PL spectra indicating that the hot carriers under both one-and two-photon excitation relax to the same lowest exciton level, from which the radiative recombination occurs.…”
Section: -mentioning
confidence: 99%
“…16 The corresponding r 2 are inferred to be 3.5 Â 10 À47 cm 4 s photon À1 (or 3.5 Â 10 3 GM) and 6.2 Â 10 À47 cm 4 s photon À1 (or 6.2 Â 10 3 GM) for QD548 and QD606, respectively, which are comparable or even larger than that of CdSe (5.1 Â 10 3 GM), CdTe (2.1 Â 10 2 GM), and CdS (4.4 Â 10 3 GM) QDs at similar sizes. 1,8,23 Interestingly, the TPA cross-sections of CdS and CdSe QDs were found to increase with size, 1,23 while those for ZnS and ZnSe QDs to decrease. 24,25 The opposite trend of TPA cross-sections of QDs with size arises from the competition between decreased quantum confinement effect and increased density of state (DOS) when the sizes of QDs increase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The third-order susceptibility of these quantum dots vary from 3.39×10 -11 to 5.77×10 -11 esu with particle size. Zhu et al [10] has also reported the colloidal CdSe nanocrystals (NCs) are successively overcoated with CdS and the effective two-photon absorption (TPA) coefficient and refractive index of this series of CdS/CdSe core/shell NCs are measured by a Z-scan technique. The effects of surface states, local field, and intrinsic piezoelectric polarization are discussed to explain the optical nonlinearity of the colloidal core/shell.…”
Section: Introductionmentioning
confidence: 98%